2017
DOI: 10.1016/j.eururo.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Four Kallikrein Panel of the 4Kscore for Prediction of High-grade Prostate Cancer in Men in the Canary Prostate Active Surveillance Study

Abstract: Active surveillance is a management strategy for many low-grade prostate cancers. Repeat biopsies monitor for previously undetected high-grade cancer. We show that a model with clinical variables, including a panel of four kallikreins, indicates the presence of high-grade cancer before a biopsy is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 16 publications
0
48
0
1
Order By: Relevance
“…35 The baseline 4Kscore also predicts reclassification on the first biopsy during active surveillance, although it did not add incremental value for prediction of subsequent surveillance biopsy outcomes. 36 …”
Section: Blood Biomarkersmentioning
confidence: 99%
“…35 The baseline 4Kscore also predicts reclassification on the first biopsy during active surveillance, although it did not add incremental value for prediction of subsequent surveillance biopsy outcomes. 36 …”
Section: Blood Biomarkersmentioning
confidence: 99%
“…Esta encuesta demuestra claramente cómo herramientas como la Bx transperineal 12,13 , la RMmp 14,15 , los software de fusión [16][17][18] y los nuevos biomarcadores [19][20][21][22] , planteadas para mejorar la caracterización inicial del tumor, están claramente infrautilizadas, pese a su potencial papel para mejorar dicha caracterización inicial descrito en la literatura, comparados o no con calculadoras de riesgo 23 . La RMmp ha mostrado claras ventajas comparada con la vía tradicional de diagnóstico de CaP y podría tener un papel en la Bx inicial 24 .…”
Section: Discussionunclassified
“…Upgrading from 3 + 3 to a higher grade, especially 3 + 4, results in a change from a low grade to high grade diagnosis and a clinically significant cancer, with possible accompanying changes in therapeutic recommendations. Studies have shown that most men who change treatment are those with GS 6 disease, as a diagnosis of GS 6 PCa can leave uncertainty about the presence of undetected aggressive disease …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that most men who change treatment are those with GS 6 disease, as a diagnosis of GS 6 PCa can leave uncertainty about the presence of undetected aggressive disease. 19,20 We recently reported the development of a combined urine/ plasma assay that has been shown to predict PCa GS ≥ 3 + 4 as compared with Bx-derived GS. This test measures the expression levels of 10 different genes in urine and plasma and incorporates these measurements in an algorithm that includes serum PSA (sPSA), prostate size, history of prior biopsy, ethnic background, and age.…”
mentioning
confidence: 99%